Diagnostic Errors for People with Autism Spectrum Disorder from the Specialists' Point of View (The International Journal for Scientific Research, 2025)
The study aimed to discern diagnostic errors and their correlation with therapeutic interventions for individuals with autism spectrum disorder from the perspective of specialists. This was examined in relation to variables such as gender, educational qualifications, years of experience, and specialization. To achieve this, the researcher employed a descriptive correlational approach, collecting quantitative data. The study instruments, encompassing diagnostic errors and therapeutic interventions, were applied to the entire specialist community in special education centers in the Ramallah and Al-Bireh governorate, totaling (255) specialists. A questionnaire consisting of thirty paragraphs was utilized and their reliability and stability were ensured.The results revealed that the overall mean for the total average of the Diagnostic Errors scale, as perceived by specialists for individuals with an autism spectrum disorder, was (3.78) with a high estimation. The mean scores on the Diagnostic Errors scale for individuals with autism spectrum disorder ranged from (1.50-4.40). The results indicated a lack of statistically significant differences at a significance level (α ≥ 0.05) among the means of the assessments of the study sample regarding the reality of Diagnostic Errors for individuals with autism spectrum disorder, as perceived by specialists. These variations were attributed to variables such as gender, educational qualifications, and specialization. However, differences emerged concerning the variable of years of experience, favoring specialists with 10 years or more of experience.In light of the study results, the researcher recommends a concerted focus on the assessment and diagnosis of autism spectrum disorder through the training of specialists in methods of measuring and diagnosing these conditions.
Keywords: Diagnostic Errors; Autism Spectrum Disorder